Implementation Of Flipped Classroom Based On Discovery Learning Model To Improve Students' Critical Thinking Skills In Temperature And Heat Materials - Rizqi Al Fajri; Muhammad Minan Chusni; Adam Malik (Pendidikan Kimia, 2026)
The development of 21st-century learning requires students to possess critical thinking skills, especially in physics, which emphasizes conceptual understanding and problem-solving. However, classroom learning is still often dominated by conventional methods that limit students' opportunities to construct knowledge actively. This study was motivated by students' low critical thinking skills during physics lessons in class XI at SMA 1 BN Baleendah. This study aims to determine the implementation of the Discovery Learning model-based Flipped Classroom to improve students' critical thinking skills on temperature and heat material. The research used a quasiexperimental design with a nonequivalent control group. Data collection was carried out using the AABTLT with the SAS instrument and a critical thinking skills test based on Ennis indicators. The population consisted of all 11thgrade students at SMA 1 BN Baleendah. The results showed that the N-Gain score in the experimental class was 0.76 (high), and in the control class, 0.69 (moderate), indicating a significant difference between the two classes. Implementing this model encourages students to become more active, independent, and enthusiastic learners. Future studies are recommended to involve larger samples and examine additional variables such as learning motivation and digital literacy.